Športno zobozdravstvo - Magdič, Marša (Šport (Ljubljana), 2022)
Sports dentistry is a field of sport medcine, that deals with the prevention and treatment of dental injuries and oral deseases linked to sport and exercise. It aims to improve oral health and is tailored for the specific demands and needs of athlets. Oral health has a direct impact on the overall health of the body and the athlets performance is dependent on it. Supervision and instruction on the oral health is one of the fundimental rights of Slovenian sportsmen and sportswomen. It is the way to help them get in their best condition and top resoults.
Keywords: šport; športne poškodbe; športniki; športno zobozdravstvo; ustno zdravje; zobje; zobozdravstvena preventiva